The Africa Agriculture Adaptation Atlas- Training workbook - Joshi, Namita; Muller, Lolita; Steward, Peter; Youngberg, Brayden (2025)
The Africa Agriculture Adaptation Atlas (https://adaptationatlas.cgiar.org/) Training Workbook is a practical, interactive manual designed to help users analyze climate risks, impacts, and adaptation options across African agriculture. It guides users through four analytical notebooks, climate hazard exposure, heat stress on producers, projected climate impacts on cereals, and climate rationale building, using step-by-step instructions, maps, key terms, and example research questions. The workbook supports users in interpreting climate data, exploring future scenarios, downloading datasets, and constructing evidence-based adaptation narratives for policy, investment, and proposal development. It strengthens capacity for data-driven climate adaptation planning across countries, crops, and production systems.